Elimination of grain boundaries and its effect on the properties of silicon nitride ceramics. Issue 8 (1st June 2020) - Hu, Feng; Zhu, Tianbin; Xie, Zhipeng; Liu, Jian; Hu, Zunlan; An, Di
Abstract: To eliminate the excess grain boundary phase in silicon nitride ceramics prepared through hot pressing and a post-sintering heat treatment, carbon was introduced into the sintered ceramics. This was accomplished in two ways: first, a small amount of carbon was used as a sintering additive; however, this creates large pores in the ceramics, resulting in a decrease in the thermal conductivity and mechanical properties of the samples. Alternatively, the C/Si3 N4 power bed could be used instead of the BN/Si3 N4 power bed, which obviously eliminates the grain boundary phase. Further, the C/Si3 N4 power bed possess excellent mechanical properties while increasing the thermal conductivity of the samples. Therefore, the silicon nitride ceramics with 123 W m −1  K −1 thermal conductivity and 986 MPa bending strength of can be obtained using the C/Si3 N4 powder bed during the post-sintering heat treatment.